2024
DOI: 10.1590/1519-6984.263815
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemistry, allelopathy and anticancer potentiality of Withania somnifera (L.) Dunal (Solanaceae)

Abstract: Withania somnifera is a wild plant that shows great activity and safety against several human diseases. The current research explored the plant's chemical composition and allelopathic effects on Rumex dentatus (recipient plant). Moreover, anticancer activity is also tested against four types of human cancer cell lines. Chemical analysis of W. somnifera showed a high percentage of saponins and tannins, while glycosides, alkaloids, and flavonoids occurred in the second order. Results of the allelopathic experime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 29 publications
(29 reference statements)
1
5
0
Order By: Relevance
“…In line with our results, Unal et al [81] reported a concentration-dependent increase in total protein content in white mustard leaves in response to the treatment with sunflower and wheat root exudates. Similarly, the increase in free amino acid content has been reported in several plant species; P. oleracea leaves after the treatment with Rumex dentatus leaf extract [82] and R. dentatus as a result of Withania somnifera root extract treatment [83]. Unlike our results, several previous publications have shown a decrease in protein and sugar content with increasing extract concentration and, thus, attributed the increased free amino acid content to the degradation of highly abundant proteins [84].…”
Section: Discussionsupporting
confidence: 85%
“…In line with our results, Unal et al [81] reported a concentration-dependent increase in total protein content in white mustard leaves in response to the treatment with sunflower and wheat root exudates. Similarly, the increase in free amino acid content has been reported in several plant species; P. oleracea leaves after the treatment with Rumex dentatus leaf extract [82] and R. dentatus as a result of Withania somnifera root extract treatment [83]. Unlike our results, several previous publications have shown a decrease in protein and sugar content with increasing extract concentration and, thus, attributed the increased free amino acid content to the degradation of highly abundant proteins [84].…”
Section: Discussionsupporting
confidence: 85%
“…Choline, which is an important nutrient required in proper functioning of various physiological processes, is present in Withania somnifera [47,48]. Withania somnifera also contains tannins [49], which are polyphenolic compounds having various uses, such as antioxidant, antiinflammatory, anticancer, and neuroprotective. Moreover, Withania somnifera also contains carbohydrates, fatty acids, and amino acids that play a significant role in maintaining daily complex biochemical processes [50].…”
Section: Chemistry Of Withania Somniferamentioning
confidence: 99%
“…Ashwagandha, the 3 rd important prioritized medicinal plant listed by National Medicinal Plant Board (NMPB) is also known as Indian Ginseng. Herbal medicines strongly involve mass appeal being safer and inexpensive [1]. An esteemed Rishi (sage) Punarvasu Atriya was the first person who gave the teaching regarding the use of ashwagandha that extends back over 3000 to 4000 years ago wherein its use is widely extolled as a tonic particularly for emaciation in all age group of people.…”
Section: Imentioning
confidence: 99%